A Critique of Control and Black Boxes: Lit Mods of Ian Hatcher's "...(Total Runout)". - Seiça, Álvaro (Poetics Today, 2020)
This article analyzes Ian Hatcher's online and kinetic poem "...(Total Runout)" (2015) from a point of view of a critique of corporate and governmental black boxing, at the level of its code, text, visual output, sound, and live performance. The multimodal poem is part of the Drone Pilot suite, and it is presented in different versions: as a web-based work, sound piece, and performance. It remixes appropriated text from a WikiLeaked manual by the UK Ministry of Defence, essays on artificial intelligence, and Hatcher's own text. The overall versions of the work, understood as variable events, boldly problematize communication and cognitive processes in networks--whether they are implemented in computer systems by secret agencies or corporations. Hatcher's critique of black boxes entails re-creating issues of security, control and surveillance, as digital systems are increasingly paving the way for less privacy and less knowledge about their inner workings. As a result, the poem questions the essence of privacy, redaction, and systemic violence, when access is a privileged asset of agents with security clearances or those with a deep knowledge of programming. This article presents "...(Total Runout)" in the scope of the poet's aesthetic program. Then, it analyzes its Web version's interface and source code. The kinetic poem's spatial and temporal dimensions are discussed via experiments that modify the source code. The methods here presented deform the poem's temporal display, by means of modifications, or what are called in the article lit mods. Thus, the article proposes an approach for a more informed reading and understanding of digital kinetic poems, since they are ever-changing events. Finally, it locates the work's aural and performative versions in a cultural and political context.